(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2021)
The present article reports part of some artistic processes, that the author developed with Cia. Teatro da Recusa, from 2017 to 2021, in which the sustainability theme was thought from the perspective of ecological worldview, with a focus on appreciation of Brazilian popular culture. These processes, which were based on observation and ethnographic research, resulted in the assembly of five works, in various techniques of puppet theatre; glove manipulation, stick, direct, balcony, giants puppets and hybrids.